Project Technology in the System of Modern Professional Education - NURULLINA, Guzel Minnezufarovna; RAMAZANOV, Ramil Kiryamovich (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to one of the topical issues of modern pedagogical science – implementation of the project technology of training of students in the system of modern professional education. The main competence formed in the course of the project technology of training is a communicative competence which is aimed at the development of speech activity of the students of different specialties. The authors consider that the indispensable culture of the expert in the hi-tech competitive world is acquisition of the skills of professional communication and use of the methods of speech influence and conviction. RESUMEN El artículo está dedicado a uno de los temas de actualidad de la ciencia pedagógica moderna: la implementación del proyecto de tecnología de capacitación de estudiantes en el sistema de educación profesional moderna. La competencia principal formada en el curso de la tecnología de capacitación del proyecto es una competencia comunicativa que está dirigida al desarrollo de la actividad del habla de los estudiantes de diferentes especialidades. Los autores del trabajo consideran que la cultura indispensable del experto en el mundo competitivo de alta tecnología es la adquisición de las habilidades de comunicación profesional y el uso de los métodos de influencia y convicción del habla.